QUALITY CONTROL IN YOGURT: ALTERNATIVE PARAMETERS FOR ASSESSMENT - Garcia, E. Segovia; Cisneros, M. G. Martinez (European Scientific Journal, ESJ, 2014)
The aim of this paper is to establish the differences in some quality parameters of different trademarks of yogurt-made manufactured products. Two methods were developed for the purpose of this study. One method consisted in allowing a sample of the product to slide down from the apex of a plastic cone and then trough a glass platform positioned at 30° over the horizontal. The other method was a comparative determination of color between samples. Duration of study 14 months. Methodology: The sliding index is based upon the fact that liquid or semisolid materials flow freely by the effect of gravity when placed above a tilted surface or above the apex of a cone, to assess the viscosity of semisolid products. The colorimetric testing shows the extreme differences of color imperceptible. The results obtained in this work show that the sliding index exhibited variable values from product to product of the same manufacturer and from batch to batch of the same product and manufacturer. The above was confirmed when both methods (cone and wedge) were used to obtain these data. The color variations were observed in a similar way as in the tests described Conclusion: The use of chromatic characterization could also be employed to study degradation of yogurt products, for it is known that many pigments used in this industry change color with time, due to either degradation, chemical instability or the effect of light.